What’s New about Canada’s Feminist International Assistance Policy and Why ‘More of the Same’ Matters - Tiessen, Rebecca (The School of Public Policy publications (Online), 2019)
Assessments of Canada’s 2017 Feminist International Assistance Policy (FIAP) are mixed. There is widespread enthusiasm for the boldness of the policy, the innovation in represents (especially in its use of the language of feminism) and its commitment to increased funding and programmatic commitments to gender equality and women’s empowerment. Critical reviews of the policy also highlight some of its limitations in terms of missed opportunities to consider broader, intersectional feminist realities, lack of clarity in approach or definitions, and insufficient translation into practice and resource allocations. The innovations and limitations of the FIAP are examined here with an additional reflection on the implications of the focus on the novelty of this policy. An empirical study of the references to the policy’s innovation highlight several elements of ‘more of the same’ in terms of renewed gender mainstreaming commitments as well as missed opportunities. The argument advanced in this paper is that ‘more of the same’ is a double-barrelled assessment reflecting the possibilities it presents for broadening and deepening long-standing Canadian commitments to gender equality as well as challenges related to ongoing limitations and weaknesses. In the longer-term trajectory of Canadian commitments to gender equality, the FIAP offers an important next step – a step that reflects, overall, ‘more of the same’ rather than the innovative feminist vision it purports to be.